Відступ держав від міжнародних зобов’язань у сфері прав людини: теорія і практика - Борисов, Євген Євгенович (Одеса, 2020)
Дисертацію присвячено міжнародно-правовим механізмам правомірного відступу держав від власних зобов’язань у сфері прав людини. Висвітлено еволюцію розуміння правомірності відступу держав від власних міжнародних зобов’язань, відображення такого відступу в сучасному праві міжнародних договорів і практику вирішення спорів щодо правомірності відступу держав від таких зобов’язань. Визначено специфіку відступу держав за універсальними та регіональними угодами у сфері прав людини, охарактеризовано процедуру та правові наслідки відступу України від власних міжнародних зобов’язань у сфері прав людини в умовах збройного конфлікту. Охарактеризовано практику оцінки правомірності відступу держав від власних зобов’язань у діяльності міжнародних судів і конвенційних органів. Відзначено ключову потребу співвідношення приписів міжнародного гуманітарного права та права прав людини в умовах дерогації, визнано вирішальну роль дотримання в умовах дерогації процесуальних прав і гарантій. Доведено, що наразі практичне значення мають механізми дерогації за Міжнародним пактом про громадянські та політичні права, за Американською конвенцією прав людини та Конвенцію про захист прав людини і основоположних свобод. Обґрунтовано, що відповідальність держави за порушення прав людини на території, яку вона не контролює, та суб’єктами, яких вона не контролює, в цілому є вкрай обмеженою. В умовах, коли держава-жертва не може гарантувати на окупованій території дотримання прав, що не підлягають дерогації, її відступ від інших зобов’язань на такій території не має практичного сенсу та формального значення. Доведено, що в Україні накопичено спеціальну законодавчу базу, в рамках якої можуть здійснюватися додаткові обмеження прав людини згідно умов дерогації, формується система відповідних правозастосовних актів.

Диссертация посвящена международно-правовым механизмам правомерного отступления государств от своих обязательств в области прав человека. Исследованы эволюция понимания правомерности отступления государств от собственных международных обязательств, отображение такого отступления в современном праве международных договоров и в практике разрешения споров о правомерности отступления государств от таких обязательств. Определена специфика отступления государств по универсальным и региональным международным соглашениям в области прав человека, охарактеризованы процедура и правовые последствия отступления Украины от собственных международных обязательств в области прав человека в условиях вооруженного конфликта. Обобщена практика оценки правомерности отступления государств от собственных обязательств в деятельности международных судов и конвенционных органов. Отмечена ключевая потребность соотнесения предписаний международного гуманитарного права и права прав человека в условиях дерогации, признана решающей роль соблюдения в условиях дерогации процессуальных прав и гарантий. Доказано, что в настоящее время практическое значение имеют механизмы дерогации в рамках Международного пакта о гражданских и политических правах, Американской конвенции прав человека, Конвенции о защите прав человека и основных свобод. Обосновано, что ответственность государства за нарушения прав человека на территории, которую оно не контролирует, и субъектами, которых оно не контролирует, в целом крайне ограничена. В условиях, когда государство-жертва не может гарантировать на оккупированной территории соблюдения базовых прав, не подлежащих дерогации, процедуры дерогации от иных его обязательств на такой территории не имеют практического смысла и формального значения. Доказано, что в Украине накоплена специальная законодательная база, в рамках которой могут осуществляться дополнительные ограничения прав человека согласно условиям дерогации, формируется система соответствующих правоприменительных актов

The dissertation is devoted to the international legal mechanisms of lawful retreat (derogation) of states from their own human rights obligations. The work reflects the development of the European scientific and philosophic doctrine on the nature of states’ obligations, including the treaty ones, of the derogation from such obligations and of its non-execution. There is proved that as minimum since the ХVІІІ century states foresaw the possibility of the derogation from their treaty obligations for humanitarian issues, such as defence the non-combatants, exchanging the prisoners of war, fishermen’s and merchants’ interests. The evolution of the understanding of the legality of the derogation of states from their own international obligations, the reflection of such derogation by the modern law of international treaties and by the practice of resolving disputes concerning the legality of the derogation of states from such obligations are also studied. The specifics of the derogation of states under universal and regional treaties in the field of human rights are defined; the procedure and legal consequences of Ukraine’s derogation from its own international human rights obligations in the context of armed conflict are described. The practice of assessing the legality of the derogation of states from their obligations in the activities of international courts and convention bodies is described. The key requirement for the correlation of the requirements of international humanitarian law and human rights under the conditions of the derogation is noted, and it recognizes the key role of observance the procedural rights and guarantees in those processes of derogation. It is proved that the mechanisms of derogation under the International Covenant on Civil and Political Rights, the American Convention on Human Rights, the Convention for the Protection of Human Rights and Fundamental Freedoms have major practical importance for the modern international law. There is determined that the state’s act regarding the derogation from its treaty obligations, including the human rights’ or their defending mechanisms’ limitation area, may be legitimate if it is the only way for state to defend own vital interests from the serious and inevitable threat. There is grounded that responsibility of states for the human rights violations at the non-controlled territories or by the noncontrolled subjects is commonly extremely limited. In conditions when the victim state can’t guarantee the execution of basic rights banned for the derogation, the procedure of possible derogation from other rights at such territory has no practical sense and formal significance. Thesis revised carefully the Ukrainian experience of derogation, including ongoing situation of the interstate conflict and reflects the derogation, done by Ukraine from obligations in framework of the Russian aggression against Ukraine, of the temporal occupation of the Autonomous Republic of Crimea and City of Sevastopol, further conflict escalation on the East of Ukraine. Such derogation covered the territories of the Donetsk and Luhansk regions being under full or partial control of Ukrainian Government. There is proved that there was no derogation by Ukraine from its obligations over the temporally occupied territories, instead of it during 2014-2015 Ukraine pointed on absence of possibility to fulfil the human rights treaties` obligations in those occupied territories. There is pointed that Ukraine formed the special legislation basis with framework that allows providing the additional limitations the human rights in compliance with the derogation conditions and that Ukraine accumulates the system of relevant legal enforcing acts.
дис. ... канд. юрид. наук : 12.00.11
Борисов Є. Є. Відступ держав від міжнародних зобов’язань у сфері прав людини: теорія і практика : автореф. дис. ... канд. юрид. наук : 12.00.11 / Є. Є. Борисов. - Одеса, 2020. - 20 с.
Keywords: дерогація; міждержавний конфлікт; міжнародні договори; міжнародні зобов`язання; надзвичайний стан; права людини; дерогация; межгосударственный конфликт; международные договора; международные обязательства; чрезвычайное положение; права человека; derogation; human rights; interstate conflict; international obligations; international treaties; state of emergency